Local Wisdom in Dideq Oral Literature among the Selayar Community in South Sulawesi - Dafirah; Pammuda; Andi Tenri Bali Baso (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Local wisdom is understood as local policy (local wisdom), local knowledge (local knowledge), or local intelligence (local genius). It may be interpreted as the product of human intellect, deep feelings, character, behavioral patterns, and moral guidance aimed at achieving human dignity. Mastery of local wisdom elevates individuals toward noble character. The concept of local wisdom held by the Selayar community is partially implemented in dideq oral texts. These concepts need to be documented, revitalized, and disseminated so that they continue to live within the community to which they belong and become part of individual character formation not only for the Selayar people, but also for the wider community of South Sulawesi and Indonesian society in general. This study aims to reveal concepts of local wisdom, particularly the attitudes of sipakatau, sipakaingaq, and sipakalabbiriq found in dideqoral literature. The primary data were collected through field research using recording, interviews, transliteration, and translation techniques. Data analysis was conducted based on Roland Barthes’ concepts of denotative and connotative meaning. The results of the study indicate that sipakatau and sipakalabbiriq are two inseparable values. Mutual respect and mutual appreciation coexist and strongly characterize the life of the Selayar community, as clearly reflected in dideq texts. Meanwhile, sipakaingaq represents an attitude of mutual reminder among community members, manifested in behavior, speech, and religious observance.